2014
DOI: 10.1016/j.displa.2014.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Navigating virtual mazes: The benefits of audiovisual landmarks

Abstract: It has been shown that multisensory presentation can improve perception, attention, and object memory compared with unisensory presentation. Consequently, we expect that multisensory presentation of landmarks can improve spatial memory and navigation. In this study we tested the effect of visual, auditory and combined landmark presentations in virtual mazes on spatial memory and spatial navigation. Nineteen participants explored four different virtual mazes consisting of nodes with landmarks and corridors conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 63 publications
(72 reference statements)
2
17
0
Order By: Relevance
“…As a control condition, we use a task in which participants had learned the smells in the learning phase and then were "beamed" to different intersections without walking the route. This method is wellestablished in spatial cognition research (e.g., Karimpur & Hamburger, 2016;Werkhoven, van Erp, & Philippi, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…As a control condition, we use a task in which participants had learned the smells in the learning phase and then were "beamed" to different intersections without walking the route. This method is wellestablished in spatial cognition research (e.g., Karimpur & Hamburger, 2016;Werkhoven, van Erp, & Philippi, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…According to the theory of multisensory perception, perception is enhanced by integrating information originating from different sensory modalities (e.g., vision, audition, and olfaction) into a unified percept (Stein & Meredith, 1993). Moreover, research has shown that congruent audiovisual landmarks enhance wayfinding performance in maze environments by reducing the distance travelled and decreasing the time travelled (e.g., Werkhoven, van Erp, & Philippi, 2014). Although it seems that auditory stimulation enhances visually presented cues mostly when the two are somehow correlated (e.g., Ardito et al, 2007), it is not yet clear how the audiovisual landmarks would affect different aspects of navigation such as wayfinding and spatial memory navigation in a complex city environment.…”
Section: Multisensory Perception In Spatial Navigationmentioning
confidence: 99%
“…The audiovisual landmarks will be congruent images and sounds that fit the city context (such as the view of a house with a garden and the sound of an automatic watering system or a visual café with the sounds of crowded conversations) and are located on the decision points of the environment. The participants in our study will perform a wayfinding task (i.e., find a specific landmark in the city environment) and two spatial memory tasks such as landmark recall and landmark localization task (Werkhoven et al, 2014). We expect better overall performance in the audiovisual landmark presentation across the different tasks based on the expected cognitive advantage due to the multisensory processing of the incoming information.…”
Section: Multisensory Perception In Spatial Navigationmentioning
confidence: 99%
“…For support of our motor behavior, we invented the lever and wheel, (motorized) machines and vehicles, and, recently, exoskeletons [10]. In order to enhance our cognitive abilities, we developed writing, the abacus for calculus, electronic computer and expert systems, e-coaches, (mobile) VR/AR environments [5,36,42,47] and brain machine interfaces [19].…”
Section: 'Human In the Loop' Systemsmentioning
confidence: 99%